The Feast of Christmas - Kelly, Joseph F. (Joseph Francis), 1945- (Book collections on Project MUSE., 2010)
Many Christians struggle to balance the religious and secular elements of Christmas, but the history of the feast shows that this is nothing new. The religious Christmas has changed over the centuries and, contrary to many critics, is thriving today. This brief, accessible account will explain that.